2015
DOI: 10.1038/mi.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Matrix protein CCN1 induced by bacterial DNA and CpG ODN limits lung inflammation and contributes to innate immune homeostasis

Abstract: Summary To defend against pulmonary infections, lung epithelial cells are equipped with complex innate immunity closely linked to inflammation. Dysregulated innate immunity / inflammation leads to self-perpetuating lung injury. The CpG motif in bacterial DNA is one of the factors involved in bacterial infection-associated inflammation. Bacterial DNA and synthetic CpG oligonucleotide (ODN) induced CCN1 secretion from lung epithelial cells, functioning as a potential “braking” signal to prevent uncontrolled infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…We observed increased phosphorylation of SRC at both the activating site (Y416) and the inactivating site (Y527). Induction of SRC phosphorylation at both tyrosine phosphorylation sites, as well as activated SRC signaling in the absence of reduced phosphorylation at Y527, has been observed by others (4547), and likely reflects heterogeneity among the cells. In our studies the dominant functional effect of RON was an overall increase in SRC activity, evidenced by a decrease in downstream SRC signaling after RON inhibition, and our observation that constitutively-activated SRC rescued resorption in osteoclasts lacking RON kinase activity.…”
Section: Discussionsupporting
confidence: 61%
“…We observed increased phosphorylation of SRC at both the activating site (Y416) and the inactivating site (Y527). Induction of SRC phosphorylation at both tyrosine phosphorylation sites, as well as activated SRC signaling in the absence of reduced phosphorylation at Y527, has been observed by others (4547), and likely reflects heterogeneity among the cells. In our studies the dominant functional effect of RON was an overall increase in SRC activity, evidenced by a decrease in downstream SRC signaling after RON inhibition, and our observation that constitutively-activated SRC rescued resorption in osteoclasts lacking RON kinase activity.…”
Section: Discussionsupporting
confidence: 61%
“…Another study suggested that CpG can induce CCN1 secretion and IL-10 release from lung epithelial cells by the BiP/GRP78-Src(Y527)-JNK-Cav-1(Y14) pathway, which can suppress TNF-α, macrophage inflammatory protein 2 (MIP-2) secretion and neutrophil infiltration in the lungs. 18 In addition, CpG can protect human monocytic cells against HIV-viral protein R (Vpr) induced apoptosis by the calcium-activated JNK pathway in a TLR9-independent manner. 24 Although pathogenesis and pathological mechanism of periodontitis are different from those diseases, these studies provide us reasons for further investigating the underlying TLR9-independent mechanism of CpG in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Moon et al have reported that endogenous lung epithelial cell-produced CCN1 exerted anti-inflammatory activity by promoting IL-10 production and by inhibiting multiple pro-inflammatory cytokines and neutrophil infiltration into the lung (25). Further, Jin et al demonstrated that suppressing CCN1 expression by siRNA accelerated lung epithelial cell death after hyperoxia, and conversely that overexpressing CCN1, conferred increased resistance to hyperoxia-induced cell death (26).…”
Section: Discussionmentioning
confidence: 99%